Biocidal and Characterization Studies of Some Newly Synthesized Co(II) Macrocyclic Complexes - Ambwani, Jitendra; Kulshreshtha, Hemant; Mittal, Vandana (Asian Journal of Chemistry, 2016)
Two new macrocylic complexes of Co(II) possessing the general formulae M[DPADTAH](BF4)2 and M[DPTDPH](BF4)2 [where M = Co(II) and [DPADTAH] = diphenyl diacetic acid-N,N'-dithio diacetic acid dihydrazone and [DPTDPH] = 2,6-diacetyl dipyridine-N,N'-thio dipropionic acid dihydrazone and (BF4)2 = tetraflouroborate. The complexes were characterized with conductance values, elemental studies, IR and electronic spectral analyses and have been assigned octahedral geometries. The in-vitro antimicrobial studies revealed that the macrocylic complexes are potentially active against bacteria S. aureus and E. coli and fungi A. flavus and C. albicans. Both the complexes exhibit greater biocidal effect as compared to the ligand fragments probably due to the greater penetration of the metal ion into cellular system of microbial strains.